Excessive use of electronic devices among children and adolescents is associated with musculoskeletal symptoms, visual symptoms, psychosocial health, and quality of life: a cross-sectional study - Sharon M. H. Tsang; Gladys L. Y. Cheing; Andrew K. C. Lam; Andrew K. C. Lam; Andrew K. C. Lam; Andrew M. H. Siu; Peter C. K. Pang; Peter C. K. Pang; Peter C. K. Pang; Kin-Chung Yip; Jess W. K. Chan; Mark P. Jensen (Frontiers in Public Health, 2023)
ObjectiveElectronic devices have become an indispensable part of our daily lives. The frequency and duration of device use in children and adolescents have increased drastically over the years and the study of its negative musculoskeletal, visual and psychosocial health impacts is necessary.Materials and methodsThis cross-sectional study aimed to evaluate the associations between electronic device use and the prevalence and severity of musculoskeletal symptoms, visual symptoms, psychosocial health, and quality of life in children and adolescents studying at primary and secondary schools. Data were collected through confidential online and paper-and-pencil questionnaires. Primary 4–5 and Secondary 1–4 students were recruited from 3 schools in Hong Kong. Demographics, frequency and duration of electronic device use, frequencies of musculoskeletal symptoms, visual symptoms, psychosocial health, and quality of life outcomes were measured.Results1,058 children and adolescents aged 9–17  years participated. Sixty-one percent and 78% of all students spent more than 2  h per day using electronic devices during school days and weekend/holidays, respectively. Extended electronic device use was associated with increased prevalence and severity of musculoskeletal symptoms (ρ’s = 0.28–0.33, P’s < 0.001), visual symptoms (ρ’s = 0.33–0.35, P’s < 0.001), and poorer device use-related psychosocial health (ρ’s = 0.38–0.47, P’s < 0.001). Secondary school students reported greater device use and severity of symptoms than primary school students.ConclusionExcessive electronic device use was associated with increased prevalence and severity of physical and psychosocial symptoms, and such use is more prevalent in adolescents when compared to the children. The findings have important health implications for children and adolescents, suggesting that early intervention is needed to reduce the risk of developing device use-related disorders.